Eosinophilic granuloma: an unusual finding in adults - Bruno F. B. B. Abreu; Marcio Luís Duarte; Murilo G. Grande; Newton M. Lima Neto; Edimeire F. Ottoni
ABSTRACT A 45-year-old man presents with occipital headache for about one month, resistant to analgesic therapy, and palpable nodule at the pain site. At initial evaluation, the nodule was 1.5 cm in diameter without apparent skin alteration. Ultrasonography revealed a well-defined osteolytic lesion and doubtful communication with the dura mater. The study was complemented with computed tomography and contrast-enhanced magnetic resonance, both identifying lytic lesion with soft tissue component and contrast enhancement, without diffusion restriction, guiding the diagnostic hypothesis of eosinophilic granuloma. Surgical treatment with mass excision and anatomopathological evaluation was made, which confirmed the radiological diagnostic hypothesis. After three months of follow-up, the patient remained symptom-free and radiographic control showed no signs of relapse.